Systematic revision and evolutionary history of Acarechimys Patterson in Kraglievich, 1965 (Rodentia, Caviomorpha, Octodontoidea) - Arnal, Michelle (2017)
The octodontoid rodent Acarechimys was abundant during the early Miocene and had the widest temporal and geographic distribution of any extinct caviomorph. Despite this extensive fossil record Acarechimys has not been well characterized. In this work, we systematically revise Acarechimys, describe new early–middle Miocene fossils from Argentina and Bolivia, corroborate its monophyly, and study its evolutionary history. Acarechimys has brachydont molars, retained deciduous premolars, four crests on upper molars, lowers with variably developed mesolophid and metalophulid II, and absence of mental foramen in the mandible. Acarechimys includes: Acarechimys leucotheae (late Oligocene, Chubut, Argentina), A. gracilis and A. constans (early Miocene, Chubut and Santa Cruz, Argentina), and A. minutus and A. minutissimus (early– middle Miocene of Patagonia Argentina, Bolivia, and Colombia). The temporal and geographic distributions suggest that Acarechimys could have evolved in Patagonia, by the early late Oligocene. Its acme was during the late early Miocene in Southern Patagonia. By the middle Miocene, Acarechimys decreased in diversity and was last recorded in high latitudes of South America (Patagonia). In lower latitudes, the oldest record is from the late early Miocene of Chucal, northern Chile, and during the late middle Miocene, the genus is recorded in localities of Colombia, Bolivia, and Peru. The available evidence suggests that Acarechimys was probably not present in lower latitudes (N of ~ 30° S) before the early Miocene. The reasons Acarechimys dispersed northward at this time remain to be elucidated, but the timing coincides with a massive disappearance of other octodontoids from Patagonia.